The Influence of Foreign Direct Investment and Exchange Rate on Foreign Exchange Reserves Through Exports in Indonesia from 2003 to 2023 (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to examine the effect of Foreign Direct Investment (FDI) and the exchange rate on exports and foreign exchange reserves in Indonesia during the period 2003–2023, with exports serving as a mediating variable. The analysis employs the path analysis method using annual data obtained from the Central Bureau of Statistics (BPS) and other relevant publications. The results indicate that FDI has a positive and significant effect on both exports and foreign exchange reserves, both directly and indirectly through exports. This finding suggests that FDI inflows contribute to increasing production capacity and export competitiveness, thereby strengthening Indonesia’s external position. Furthermore, exports are found to have a positive and significant effect on foreign exchange reserves, reaffirming their strategic role in maintaining external stability. Conversely, the exchange rate has a negative but statistically insignificant effect on exports and foreign exchange reserves, indicating that rupiah depreciation does not automatically enhance export performance or increase foreign exchange reserves. This condition is likely due to the domestic industry’s reliance on imported raw materials and capital goods, as well as the dominance of primary commodities in Indonesia’s export structure. Overall, the findings highlight the need for policies that promote FDI in export-oriented sectors, diversify export products, develop import-substitution industries, and improve trade logistics efficiency to optimize the role of exports in strengthening Indonesia’s foreign exchange reserves.